Students' Visual Challenges in Interpreting Geometric Elements in Batik Motifs - Winahyu Septiana Prayogi; Muhammad Noor Kholid (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to identify and analyze the visual challenges faced by elementary school students in identifying geometric elements in Sukowati batik motifs.Methodology: Using a qualitative approach with an ethnographic design, data were collected from 12 fifth-grade students at Elementary School in Sragen, Central Java, through visual-based math tests, in-depth interviews, and observations.Results: The results show that students experience visual challenges in describing geometric shapes, including an inability to distinguish between parallelograms and isosceles triangles, confusion in distinguishing rhombuses from squares, and difficulty in recognizing basic geometric shapes due to overlapping decorative elements and complex ornamental patterns.Applications/Originality/Value: This study provides a basis for developing locally-based learning strategies by utilizing batik as a contextual medium to improve students' understanding of geometry and visual-spatial competence.